2021
DOI: 10.1159/000519772
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of an Expanded Disability Status Scale Model in Multiple Sclerosis

Abstract: <b><i>Introduction:</i></b> We aimed to develop and validate an Expanded Disability Status Scale (EDSS) model through clinical, optical coherence tomography (OCT), and magnetic resonance imaging (MRI) measures. <b><i>Methods:</i></b> Sixty-four multiple sclerosis (MS) patients underwent peripapillary retinal nerve fiber layer and segmented macular layers evaluation through OCT (Spectralis, Heidelberg Engineering). Brain parenchymal fraction was quantified through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
(99 reference statements)
0
9
0
Order By: Relevance
“…Our results are in accordance with certain previous studies that a higher compliance to MD may be associated with an improvement in disease disability and symptom severity, exerting also positive effects in several aspects of the mental health of older adults with MS such as depression, anxiety, and stress, reinforcing also daily quality of life, sleep quality and physical activity. [40][41][42][43][44][45][46][47][48][49] In this context, recent high-quality evidence has strongly supported that MD can exert anti-inflammatory and antioxidants effects against human diseases, including MS. [50][51][52] Notably, an update of the Cochrane Review 'Dietary interventions for MS has suggested that there is insufficient evidence to determine whether supplementation with antioxidants or other dietary interventions have any impact on MS-related outcomes, while some of the currently available studies suffers from high risk of bias at present. 60 Beyond MD, a recently published study found that a paleo diet, may be useful in MS treatment by reducing perceived fatigue, improving mental and physical quality of life, increasing exercise capacity, and improving arm and leg function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results are in accordance with certain previous studies that a higher compliance to MD may be associated with an improvement in disease disability and symptom severity, exerting also positive effects in several aspects of the mental health of older adults with MS such as depression, anxiety, and stress, reinforcing also daily quality of life, sleep quality and physical activity. [40][41][42][43][44][45][46][47][48][49] In this context, recent high-quality evidence has strongly supported that MD can exert anti-inflammatory and antioxidants effects against human diseases, including MS. [50][51][52] Notably, an update of the Cochrane Review 'Dietary interventions for MS has suggested that there is insufficient evidence to determine whether supplementation with antioxidants or other dietary interventions have any impact on MS-related outcomes, while some of the currently available studies suffers from high risk of bias at present. 60 Beyond MD, a recently published study found that a paleo diet, may be useful in MS treatment by reducing perceived fatigue, improving mental and physical quality of life, increasing exercise capacity, and improving arm and leg function.…”
Section: Discussionmentioning
confidence: 99%
“…The Expanded Disability Status Scale (EDSS) is a validated and well-recognized method of quantifying disability in MS and monitoring changes in the level of disability over time. 52 EDSS steps 1.0 to 4.5 refer to patients who are fully ambulatory, while EDSS steps 5.0 to 9.5 are defined by the impairment to ambulation and usual equivalents and impairment to walking. 52 Depression status was assessed using the Geriatric Depression Scale (GDS) questionnaire which includes 30 items.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various quantitative measures (i.e., the number and volume of contrast-enhancing, the volumes of T2-hyperintense and T1-hypointense lesions, and brain volume changes), derived from conventional and advanced MRI methods, have been proposed as prognostic biomarkers for MS. However, correlations between different MRI indicators and EDSS are not satisfactory, and no specific MRI measure is used as a comprehensive prognostic imaging biomarker for MS [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%